(untitled) (Praxis Educativa, 2021)
This article compares the school performance of low-income students who attend schools where they represent small minorities with the average performance of students from the same social sector. To do this, it uses data from the Argentine chapter of the PISA 2018 bases. Based on them, it analyzes the performance of students by economic, social and cultural level, first comparing all students and then only those who attend schools where low-income students are small minorities. The results show that this group of students achieves higher than average performances. Although the study does not reach definitive conclusions, it suggests that the cultural and educational resources available to these students, plus the social composition and institutional characteristics of the schools they attend, could explain the higher levels of achievement.